IMPLEMENTASI AFFIRMASI KEBIJAKAN PENGELOLAAN DANA DESA DALAM PEMBANGUNAN DESA - Murliasari, Rikha (Jurnal Bina Praja, 2021)
The pendulum direction of development which initially only leans in the city is now directed to rural areas. Affirmation of government policies to villages is evidenced by the distribution of Village Funds since 2015. This study aims to find out how the implementation of village fund management in village development is through the role of village governments with an approach to rights of origin and local authority on a village scale. This study uses an explanatory approach by combining a case study design with a comparative study, which focuses on conducting an in-depth study on the role of village government in village development in Sirnagalih Village, Cipongkor District, West Bandung Regency. Data sources include the Village Head, Village Apparatus, Regional Personnel, and Training Agency, Village Community Institutions and Village Traditional Institutions, Community Leaders, Head of Subdistrict and Echelon Officials in the subdistrict, Head of Regency Village Community Empowerment Service and Echelon Officials at the Village Community Empowerment Service, as well as elements of the Community. The data analysis method used was qualitative analysis. The analysis results show that village development has a very strategic role in spurring regional development. It happens because it contains elements of equitable distribution of development and its results and directly touches the interests of the majority of the people who live in rural areas. It was found that village development programs and activities responsive to Community need to have resulted in high community participation. Therefore, the optimization of development implementation is influenced by community participation activities in implementing and preserving development results. For this reason, the main solution that needs to be given to the problem of managing Village Funds in Village development is the application of policy affirmations in the management of Village Funds.